THE RIGHT OF PEDAGOGICAL VETO: DEVELOPING CRITICAL REFLECTION SKILLS IN FUTURE TEACHERS WHEN WORKING WITH GENERATIVE ARTIFICIAL INTELLIGENCE 'HALLUCINATIONS' - Xasanov Z.Sh. (Uzbekistan Open Conference, 2026)
The rapid integration of large language models (LLM) into pedagogical practice highlights the problem of critical assessment of machine-generated content by future teachers. This article presents the results of a quasi-experimental study aimed at developing a reflective-personal mechanism in educators working with generative AI tools. Based on the author's platform 'Lesson and Task Generator', the effectiveness of the peer-review methodology and professional reflective journals (RJS-2024) has been proven. The study demonstrates that controlled exposure of future teachers to AI 'hallucinations' is a powerful catalyst for developing their professional expertise and responsibility.
Keywords: generative artificial intelligence; critical thinking; pedagogical reflection; AI hallucinations; teacher training; peer-review; AI ethics in education